A geo-thermochronological study offshore west of Ireland: the timing of exhumation and magmatic activity and the nature of the basement on the Irish Atlantic Margin - Rateau, Rémi (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2021)
In recent years, the use of multiple low-temperature thermochronometers combined with inverse thermal history modelling of multiple samples on vertical profiles has been shown capable of detecting low magnitude exhumation events that characterise many passive margins. Such approaches have shed new insights on the Mesozoic and Cenozoic exhumation history of onshore Ireland and Britain. A similar approach has been used in this study to investigate the exhumation history of the Irish Atlantic Margin (IAM), the southern segment of the North-East Atlantic Margin, which until now has been primarily studied by apatite fission track dating in isolation. More than 40 new samples (from PAD and Ifremer) were acquired from borehole cuttings and cores and seabed dredge samples all along the IAM (from the Donegal and NE Rockall basins to the north to the southern tip of the Porcupine High and the Goban Spur to the south). After compiling all the low-temperature thermochronological data from Ireland and the UK, a set of legacy AFT and AHe samples was also selected to complement the new samples, as half of the samples collected in this study did not yield enough apatite. Zircon and apatite U/Pb dating and apatite trace element determinations were undertaken to constrain the thermal history model and derive new insights on the timing of magmatism and nature of the basement offshore west of Ireland. The thermal histories derived from the thermochronological data show that the investigated segments of the IAM are dominated by Late Jurassic and Early Cretaceous cooling associated with the main phases of rifting and hyperextension in the Porcupine and Rockall basins and between the Celtic margin and its conjugate margins (North Iberia and Canada). North to south diachronous Mesozoic cooling and exhumation has been observed in thermal histories employing vertical profiles on earlier studies on the western Ireland onshore. This study shows that such a trend is not observed on the IAM. Instead, the AFT age spatial pattern complied from the new data and legacy data from Ireland and Britain points towards differential exhumation of the IAM on either side of the Anton-Dorhn Transfer Zone and its extension onto the onshore, with more exhumation observed up to the end of the Early Cretaceous on the SW, ocean-side of the lineament; while shorter-wavelength rift-shoulder uplift would explain some of the younger ages observed north of the lineament. The regional Caledonian faults were also a likely major influence. Tectonic blocks/terranes bounded by these faults seem to respond differently to the Mesozoic exhumation as observed on an AFT age map of Northern Scotland. This observation could also explain some of the dispersion seen in the exhumation trends of spatially close samples in the North Porcupine High. A regional Late Paleocene-Early Eocene exhumation event was not detected in the northern part of the IAM despite the inferred presence of a thick body of underplated igneous rock, but has been detected on the North Porcupine High as was predicted by earlier subsidence modelling studies in the North Porcupine Basin. A km-scale Miocene exhumation event was confirmed in the northern part of the study area but was found to be absent south of the Slyne Basin. The new geochronological dataset has led to the discovery of Dalradian metasedimentary rocks on Finnian?s Spur, on the eastern edge of the North Porcupine High. These metasedimentary rocks were affected by a Caledonian tectonothermal event. A 1.7 Ga basement unit on the NW flank of the North Porcupine High has also been detected, while earlier interpretations of a granite at the bottom of a borehole on the eastern margin of the North Porcupine Basin have been reappraised as a Caledonian metaconglomerate sourced from the Grampian Belt. The age of Late Variscan granitoids that crop out on the southern tip of the Goban Spur (4000 m water depth) have been confirmed by the new apatite and zircon dating. The apatite trace element data suggests an I-type granite affinity, unlike the S-type Late Variscan granites of the Cornubian Batholith located to the NE on the same Caledonian lineament. A Cadomian granulite likely represents the local basement to these granites, while an Archean metamorphic rock with Middle Eocene AFT and AHe ages recovered from the Goban Spur is believed to represent an ice-rafted clast derived from the Archean basement of Scotland or Greenland. Similarly, a gneiss from the southern tip of the Porcupine High yielded a Mesoarchean crystallisation age and Permian AFT age and is believed to be an ice-rafted clast. In the same area, a Mesoproterozoic metagabbro and a Late Caledonian granite both yield Triassic AFT ages. They may represent in-situ basement but additional dating of samples from this area would be required to be confirm this. This study also presents new geochronology data from previously undated igneous rocks from the IAM. An undated gabbro in a borehole located offshore NW Donegal (13/03-1) was dated at 297 Ma and is interpreted as a tilted gabbroic dyke that may represent the westernmost extension of the latest Carboniferous-earliest Permian tholeiitic Scottish dyke swarm. A sandstone from the eastern margin of the North Porcupine Basin (26/30-1) was revealed to be of tuffaceous origin and yielded Oxfordian volcanic apatite, while an undated dolerite from the Slyne Basin (18/25-2) was dated as Late Jurassic to Early Cretaceous. A sill of probably Paleogene age and previously interpreted as a sandstone was discovered in a borehole on the eastern margin of the North Porcupine High (34/05-1). The Late Oligocene age of three sills in a borehole from the Porcupine Basin (35/13-1) has been revised to Danian-Selandian, while the sills and lava flows from a nearby borehole (35/15-1) revealed a probable Danian age for the mafic magmatism but also Selandian zircons that are interpreted as sourced from a tuffaceous microconglomerate just above the basalts.
APPROVED
Keywords: geochronology; thermochronology; LA-ICP-MS; apatite fission track; Irish Atlantic margin; exhumation; U/Pb dating; offshore Ireland